2017
DOI: 10.1016/j.ijsu.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of minimally invasive radioguided parathyroidectomy using very low intraoperative dose of Tc-99m MIBI

Abstract: The MIRP technique using very low dose (1 mCi) of Tc-99m MIBI without intraoperative PTH assay and frozen section analysis resulted in excellent cure rate for PHPT. This technique involves a radiation exposure to patients and surgical staffs 20 times lower than conventional MIRP using 20 mCi Tc-99m MIBI. Besides, patients with PHPT due to ectopic parathyroid adenoma may especially benefit from MIRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…CT can detect lesions over 1.5 cm in size. Although reviews are reporting that intraoperative gamma probes can be used for small-sized lesions [7], some surgeons suggest that this method will not be beneficial due to large vessels and heart activities [8]. Intravenous methylene blue is another option to localize ectopic glands.…”
Section: Discussionmentioning
confidence: 99%
“…CT can detect lesions over 1.5 cm in size. Although reviews are reporting that intraoperative gamma probes can be used for small-sized lesions [7], some surgeons suggest that this method will not be beneficial due to large vessels and heart activities [8]. Intravenous methylene blue is another option to localize ectopic glands.…”
Section: Discussionmentioning
confidence: 99%
“…A 99mTc sestamibi parathyroid scan and computed tomography of both the neck and the thorax can easily localize the ectopic parathyroid adenoma. Intraoperative radio-guided navigation with a gamma probe can be used for perioperative localization in smaller lesions [ 27 , 28 ]. Alesina et al [ 18 ] considered that the use of a gamma probe could be helpful for reducing the operation time.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been reported that radio-guided detection techniques were developed for surgical treatment of parathyroid adenomas. The MIRP (minimally invasive radio-guided parathyroidectomy) technique allows a low dose (1 mCi) of Tc-99m MIBI without intraoperative PTH assay and frozen section analysis leading to excellent cure rate for PHPT (15).…”
Section: Discussionmentioning
confidence: 99%